PEUTZ JEGHERS SYNDROME PRESENTING WITH ACUTE INTESTINAL OBSTRUCTION: A RARE CASE REPORT WITH REVIEW OF LITERATURES - Hota, P. K.; Reddy, G. Narasimha; Rajasekhar, G.; Mohan, C. Nalini (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Peutz-Jeghers syndrome is a rare genetic disorder presenting in young age with mucocutaneous pigmentation and hamartomatous polyposis. Method: We report a case of PeutzJeghers syndrome in a 16 year old boy presenting with acute intestinal obstruction. Results: Imaging studies revealed intussusception. He had mucocutaneous pigmentation and multiple hamartomatous polyps which were diagnosed histologically. The unusual presentation of the case and its successful management has prompted us to report the case with literature review.
Keywords: Peutz-Jeghers syndrome, intussusception, acute intestinal obstruction.